Quantitation of 47 human tear proteins using high resolution multiple reaction monitoring (HR-MRM) based-mass spectrometry - Tong, Louis; Zhou, Xi Yuan; Jylha, Antti; Aapola, Ulla; Liu, Dan Ning; Koh, Siew Kwan; Tian, Dechao; Quah, Joanne; Uusitalo, Hannu; Beuerman, Roger W.; Zhou, Lei (Journal of proteomics, 2015)
Tear proteins are intimately related to the pathophysiology of the ocular surface. Many recent studies have demonstrated that the tear is an accessible fluid for studying eye diseases and biomarker discovery. This study describes a high resolution multiple reaction monitoring (HR-MRM) approach for developing assays for quantification of biologically important tear proteins. Human tear samples were collected from 1000 subjects with no eye complaints (411 male, 589 female, average age: 55.5±14.5years) after obtaining informed consent. Tear samples were collected using Schirmer's strips and pooled into a single global control sample. Quantification of proteins was carried out by selecting “signature” peptides derived by trypsin digestion. A 1-h nanoLC-MS/MS run was used to quantify the tear proteins in HR-MRM mode. Good reproducibility of signal intensity (using peak areas) was demonstrated for all 47 HR-MRM assays with an average coefficient of variation (CV%) of 4.82% (range: 1.52–10.30%). All assays showed consistent retention time with a CV of less than 0.80% (average: 0.57%). HR-MRM absolute quantitation of eight tear proteins was demonstrated using stable isotope-labeled peptides. In this study, we demonstrated for the first time the technique to quantify 47 human tear proteins in HR-MRM mode using approximately 1μl of human tear sample. These multiplexed HR-MRM-based assays show great promise of further development for biomarker validation in human tear samples. Both discovery-based and targeted quantitative proteomics can be achieved in a single quadrupole time-of-flight mass spectrometer platform (TripleTOF 5600 system). [Display omitted] •We establish 47 high-resolution MRM assays representing 47 human tear proteins using only 1μl of human tears.•HR-MRM absolute quantitation of eight human tear proteins (S100 A9, S100 A11, ENO1, DMBT1, HSPB1, HSPA1B, LDHA, and LDHB).•Discovery proteomics and targeted quantitative proteomics can be achieved using a single mass spectrometer platform.